2019
DOI: 10.5614/j.eng.technol.sci.2019.51.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Void Detection System using Gamma-Ray Compton Scattering Technique

Abstract: A simple void detection system for concrete was successfully developed using high-penetration gamma rays with Compton scattering. This research attempted to identify a void in the subsurface of a concrete volume that could not be accessed from any of the sides. Monte Carlo simulation using GEANT4 toolkit was performed to investigate the gamma-ray backscattering events. An NaI(Tl) detector was used with 60 Co and 137 Cs as gamma-ray sources. The void's location was successfully detected during material target s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results showed that steel inclusions and defects with a radius of 4 mm within 2 cm from the sample surface could be detected. In 2019, Sari et al [19] compared and analyzed the detection effects of Co-60 and Cs-137 radiation sources on cavities in concrete volume. The results showed that Cs-137 radiation source is more effective in the Compton scattering nondestructive testing system.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that steel inclusions and defects with a radius of 4 mm within 2 cm from the sample surface could be detected. In 2019, Sari et al [19] compared and analyzed the detection effects of Co-60 and Cs-137 radiation sources on cavities in concrete volume. The results showed that Cs-137 radiation source is more effective in the Compton scattering nondestructive testing system.…”
Section: Introductionmentioning
confidence: 99%